Controle de movimento com músculo pneumático através de sinais eletromiográficos de superfície - Viapiana, Marciel (2018)
This work proposes the use of pneumatic muscle, whose shape and behavior characteristics resemble the human muscle, for the continuous control of the positioning of a bench manipulator, being controlled by the intensity of the muscular effort of the user, read by surface electromyographic sensors. The association of the electromyographic signals with the pneumatic muscle aims to make the movement artificially generated as close as possible to the natural one, facilitating the user's adaptation to the use of this assistive technology. For the tests with the built bench, a geometric model for the manipulator was defined to meet the characteristics of the pneumatic muscle type actuator and to be representative in relation to the angular stroke. Based on the defined geometry, a bench was built, which has an aluminum rod representing the forearm, and a pneumatic muscle type actuator, which represents the action of the muscle needed for movement. To control the position of the manipulator through the action of the pneumatic muscle, it is necessary to control the feeding pressure of this, which is done by a manual pressure regulating valve, which has been automated, so that the control can be done electrically. For control of the automated valve, a PID controller has been tuned. In order to evaluate the characteristics of the workbench, a manipulator positioning test was performed, which allowed the observation and quantification of its proper functioning. Finally, the electromyographic signal was inserted into the control algorithm as a reference for positioning, which allows the user to control the pressure with which the actuator will be fed through the biceps muscle effort and consequently the angular position assumed by the manipulator on the bench. These tests allowed to evaluate the quality with which one can control the position of the manipulator, using surface electromyographic signals, resulting in an angular variation of less than 10 degrees around the desired position, the main origin of this variation being the characteristics of the developed bench.